2016
DOI: 10.4081/or.2016.6256
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of osteoarthritis of the knee with bracing: a scoping review

Abstract: Knee osteoarthritis is a leading cause of disability around the world. Knee bracing provides a conservative management option for symptom relief. A variety of different bracing types, manufacturers and products are currently available on the market. The goal of this study is to examine the current state of the literature regarding the treatment of knee osteoarthritis with unloader bracing, specifically examining the representation of specific brace types, manufacturers and models within the literature.A scopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Exercise helps to strengthen the muscle around the affected joints, which, in turn, reduces pain and instability in patients. There is also some evidence that patients can benefit from knee braces and shoe orthotics [20]. Aside from these non-pharmacological suggestions, patients may benefit from nonsteroidal anti-inflammatory drugs (NSAIDS) as well as intra-articular inoculations of corticosteroids and hyaluronic acid (HA) [21,22].…”
Section: Treatment Approachesmentioning
confidence: 99%
“…Exercise helps to strengthen the muscle around the affected joints, which, in turn, reduces pain and instability in patients. There is also some evidence that patients can benefit from knee braces and shoe orthotics [20]. Aside from these non-pharmacological suggestions, patients may benefit from nonsteroidal anti-inflammatory drugs (NSAIDS) as well as intra-articular inoculations of corticosteroids and hyaluronic acid (HA) [21,22].…”
Section: Treatment Approachesmentioning
confidence: 99%
“…Numerous studies have been published on the effi cacy of unloader bracing in knee osteoarthritis, and although a recent scoping review identified that 92% of studies supported their use, 94% of available research was nonrandomized or based upon expert opinion. 20 A metaanalysis of six RCTs comparing the use of a medial unloader knee brace for the treatment of medial compartment arthritis to a control orthosis found a small, statisti cally significant benefit favouring the brace for improvement in pain (standardized mean difference [SMD] 0.33, 95% CI 0.13 to 0.52) and function (SMD 0.22, 95% CI 0.02 to 0.41). 21 Because of the low quality of available evidence, the clinical importance of these findings remains unclear.…”
Section: Weight Lossmentioning
confidence: 99%
“…Knee braces are a common conservative treatment option for reducing pain and improving function in people with musculoskeletal injuries and disease (Chew et al, 2007 ), such as knee osteoarthritis (OA) (Ramsey and Russell, 2009 ; Petersen et al, 2016 ; Phillips et al, 2016 ). Unicompartment off-loader braces are a common style of knee brace designed to reduce pain and progressive degeneration of the osteoarthritic knee by redistributing compressive forces away from the diseased medial or lateral tibiofemoral (TF) compartment via joint realignment (Ramsey et al, 2007 ; Briem and Ramsey, 2013 ).…”
Section: Introductionmentioning
confidence: 99%